Effect of face masks on dyspnea perception, cardiopulmonary parameters, and facial temperature in healthy adults - Ramoti, Natanael; Siahaan, Andre MP.; Indharty, Suzy; Adella, Cut A. (Narra J, 2024)
Respiratory droplets, naturally produced during expiration, can transmit pathogens from infected individuals. Wearing a face mask is crucial to prevent such transmission, yet the perception of dyspnea and uncomfortable breathing remains a common concern, particularly during epidemics. The aim of this study was to investigate the impact of face mask use on the perception of dyspnea, cardiopulmonary parameters, and facial temperature during physical activity. A randomized crossover study was conducted on healthy adults at a physiology laboratory located in the Faculty of Medicine, Universitas Sumatera Utara, Medan, Indonesia, in November 2022. Participants underwent five stages of physical exercise tests based on the Bruce Protocol under three conditions: without any face mask (control), wearing a surgical mask, and an N95 mask, forming the study's main groups. Dyspnea perception (measured by the Modified Borg Dyspnea Scale), cardiopulmonary parameters (heart rate, oxygen saturation, respiratory rate, blood pressure, and mean arterial pressure) and facial temperature were measured before the exercise test (pre-workout), at the end of stage 1, 2, 3, 4, 5, and after the whole exercise test (post-workout). A two-way repeated measures ANOVA was conducted, considering two factors: the type of mask (control, surgical mask, N95 mask) and the various stages of the exercise test. A total of 36 healthy adults were included in the study. We found that dyspnea perception was much worse in the N95 mask group, particularly during vigorous exercise. There was no significant difference between groups in cardiopulmonary parameters. However, participants wearing N95 had a greater supralabial temperature than those wearing surgical masks or no mask at all. It is recommended to undertake a more in-depth evaluation of cardiopulmonary physiological measures.